Regulation of Transcription of the Bacillus subtilis pyrG Gene, Encoding Cytidine Triphosphate Synthetase - Meng, Qi (American Society for Microbiology, 2001)
The B. subtilis pyrG gene, which encodes CTP synthetase, is located far from the pyrimidine biosynthetic operon on the chromosome and is independently regulated. The pyrG promoter and 5′ leader were fused to lacZ and integrated into the chromosomes of several B. subtilis strains having mutations in genes of pyrimidine biosynthesis and salvage. These mutations allowed the intracellular pools of cytidine and uridine nucleotides to be manipulated by the composition of the growth medium. These experiments indicated that pyrG expression is repressed by cytidine nucleotides but is largely independent of uridine nucleotides. The start of pyrG transcription was mapped by primer extension to a position 178 nucleotides upstream of the translation initiation codon. A factor-independent termination hairpin lying between the pyrG promoter and its coding region is essential for regulation of pyrG expression. Primer-extended transcripts were equally abundant in repressed and derepressed cells when the primer bound upstream of the terminator, but they were much less abundant in repressed cells when the primer bound downstream of the terminator. Furthermore, deletion of the terminator from pyrG-lacZ fusions integrated into the chromosome yielded elevated levels of expression that was not repressible by cytidine. We suggest that cytidine repression of pyrG expression is mediated by an antitermination mechanism in which antitermination by a putative trans-acting protein is reduced by elevated levels of cytidine nucleotides. Conservation of sequences and secondary structural elements in the pyrG 5′ leaders of several other gram-positive bacteria indicates that their pyrG genes are regulated by a similar mechanism.